2021
DOI: 10.1017/jfm.2021.414
|View full text |Cite
|
Sign up to set email alerts
|

Viscid–inviscid interactions of pairwise bubbles in a turbulent channel flow and their implications for bubble clustering

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…31,32 Researchers have also employed the VOF method to study the effects of fluid properties, operating conditions, and orifice size on single bubble formation and multibubble interactions in water. 33,34 Newly developed models for bubble coalescence and breakup are proposed by Rzehak et al 35 A two-step procedure was used for model validation; in the first step, the bubble size distribution was replaced by measured values. In the second step, a previously qualified model of bubble forces and bubbleinduced turbulence was used without any changes and allowed assessment of the validity of the bubble coalescence and breakup model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Researchers have also employed the VOF method to study the effects of fluid properties, operating conditions, and orifice size on single bubble formation and multibubble interactions in water. 33,34 Newly developed models for bubble coalescence and breakup are proposed by Rzehak et al 35 A two-step procedure was used for model validation; in the first step, the bubble size distribution was replaced by measured values. In the second step, a previously qualified model of bubble forces and bubbleinduced turbulence was used without any changes and allowed assessment of the validity of the bubble coalescence and breakup model.…”
Section: Introductionmentioning
confidence: 99%
“…Through CFD simulations, bubble interactions at the microscopic level can be observed and quantified and parameters such as the initial bubble diameter and spacing can be conveniently adjusted, thereby obtaining insights that traditional experimental methods often fail to provide. Given its ability to track interfaces, the volume of fluid (VOF) model is widely used in the studies of single bubble motion, multibubble behavior, and associated mass transfer processes. , Through the application of VOF, Liu et al numerically investigated the coalescence and breakup process of multiple parallel bubbles in a power-law fluid and the interaction between three equally spaced parallel bubbles in a non-Newtonian fluid, and analyzed the mechanism of coalescence and breakup of parallel bubbles. , Researchers have also employed the VOF method to study the effects of fluid properties, operating conditions, and orifice size on single bubble formation and multibubble interactions in water. , Newly developed models for bubble coalescence and breakup are proposed by Rzehak et al A two-step procedure was used for model validation; in the first step, the bubble size distribution was replaced by measured values. In the second step, a previously qualified model of bubble forces and bubble-induced turbulence was used without any changes and allowed assessment of the validity of the bubble coalescence and breakup model.…”
Section: Introductionmentioning
confidence: 99%
“…They are present in most multiphase systems, being either present naturally or else introduced purposefully (Levich 1962;Stone 1994;Soligo, Roccon & Soldati 2019;Lohse 2022). In bubbly flows, it has been shown that even small amounts of surfactant can cause dramatic changes to the bubble shapes (Tomiyama et al 2002;Tagawa, Takagi & Matsumoto 2014;Hessenkemper et al 2021a), bubble rise velocities (Bel Fdhila & Duineveld 1996;Cuenot, Magnaudet & Spennato 1997;Takagi, Ogasawara & Matsumoto 2008;Tagawa et al 2014), lateral migration (Lu, Muradoglu & Tryggvason 2017;Hayashi & Tomiyama 2018;Ahmed et al 2020;Atasi et al 2023), cluster formation (Takagi et al 2009;Maeda et al 2021;Ma et al 2023), coalescence (Verschoof et al 2016;Lohse 2018;Néel & Deike 2021) and mass transfer on the interfaces (Cuenot et al 1997;Schlüter et al 2021). Some of the aforementioned effects can also occur due to the presence of salt in the liquid phase (Craig, Ninham & Pashley 1993;Gvozdić et al 2019;Hori et al 2020;Blaauw, Lohse & Huisman 2023), However, the mechanisms producing these effects are different in that case.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) There is strong enhancement of the turbulent kinetic energy dissipation rate in the vicinity of the bubble surface (Santarelli, Roussel & Fröhlich 2016;du Cluzeau, Bois & Toutant 2019). (iv) The energy spectra in either the frequency or wavenumber space exhibit a −3 power-law scaling for a subrange for all the components of the fluctuating fluid velocity (Ma et al 2017;Pandey, Ramadugu & Perlekar 2020;Innocenti et al 2021). (v) Pandey et al (2020) and Innocenti et al (2021) showed that on average, the energy transfer is from large to small scales in BIT; however, there is also evidence of an upscale transfer when considering the transfer of energy associated with particular components of the velocity field .…”
Section: Introductionmentioning
confidence: 99%